Prevalence of and barriers to dual-contraceptive methods use among married men and women living with HIV in India. - Chakrapani, Venkatesan; Kershaw, Trace; Shunmugam, Murali; Newman, Peter A; Cornman, Deborah H; Dubrow, Robert (Infectious diseases in obstetrics and gynecology, 2011)
To describe the prevalence and correlates of dual-contraceptive methods use (condoms and an effective pregnancy prevention method) and barriers to their use among married persons living with HIV (PLHIV) in India.
Keywords: Adolescent; Adult; Condoms; Contraception Behavior; Family Planning Services; Female; Focus Groups; Health Knowledge, Attitudes, Practice; Health Services Accessibility; HIV Infections; Humans; India; Male; Young Adult